Inter-rater reliability of the hand activity level using cyclic and non-cyclic tasks - Gober, Jennifer, author; Rosecrance, John, advisor; Gilkey, David, committee member; Fitzhorn, Patrick, committee member (Colorado State University. Libraries, 2010)
Research has shown a link between exposure to excessive repetitive motion and the development of musculoskeletal disorders. Exposure assessment tools have been developed to measure risk factors, such as repetitive motion, and their relationship to health outcomes. To accurately evaluate risk factors, a tool must be both valid and reliable. The present study evaluated the inter-rater reliability of the Hand Activity Level (HAL), which is one portion of the ACGIH TLV for hand activity. Workers from a large appliance manufacturing facility were video recorded and assessed on a HAL rating scale by two independent raters. The HAL was originally designed to be used for tasks cyclic in nature, however, in the present study non-cyclic tasks were also rated. Work task HAL ratings were compared across raters using a weighted Pearson Product Moment Correlation Coefficient. Fair to moderate inter-rater reliability was found for both cyclic and non-cyclic tasks. A paired t-test was used to determine if there was a significant difference in correlation coefficients between HAL ratings for cyclic and noncyclic tasks. No significant difference was found between the correlation coefficients of cyclic and non-cyclic tasks. The present study found that the HAL is a reliable measure for both cyclic and non-cyclic tasks. Additional studies should be conducted to determine if the HAL is a valid measure of repetition in non-cyclic tasks.
Keywords: Overuse injuries; Overuse injuries -- Prevention; Hand -- Wounds and injuries